Ethiopia Productive Safety Net Program (PSNP) Business Enterprise Survey, 2013 - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
The PSNP business survey collected data from select businesses in 8 communities studies where PSNP is active. The purpose of the survey was to provide researchers with the data necessary to construct Local Economy-wide Impact Evaluation (LEWIE) models used for evaluation of the PSNP program. In particular, the survey collected data about hired labor necessary to accurately model production functions in LEWIE, as well as input and output markets.